Behavioral Activation and Acceptance and Commitment Therapy in the Treatment of Anxiety and Depression in Cancer Survivors: A Randomized Clinical Trial. Issue 5 (September 2021) - Fernández-Rodríguez, Concepción; González-Fernández, Sonia; Coto-Lesmes, Rocío; Pedrosa, Ignacio
Behavioural Activation (BA) and Acceptance and Commitment Therapy (ACT) aim to reduce the inflexible avoidance of painful thoughts, feelings and memories and to encourage involvement in relevant activities, objectives which are clearly relevant to the situation of cancer survivors with emotional problems. With a view to evaluating and comparing the efficacy of both therapies, applied on a group basis, a randomized controlled trial was developed. Cancer survivors (age 18–65 years) with anxiety and/or depression were assigned at random to two experimental groups (BA; ACT) and a waiting list control group (WL). Of the 66 cancer survivors randomized to trial (intention-to-treat sample), 46 participants ( M = 51.49; SD = 6.88) completed the intervention (BA, n = 17; ACT, n = 12; WL, n = 17) (per-protocol sample). The emotional state, experiential avoidance and behavioural activation of the participants was evaluated in the pre- and post-treatment and in a 3-month follow-up using standardized instruments. Both treatment groups showed statistically significant changes, indicating an improvement in all the result variables in the post-treatment and follow-up as compared to the pre-treatment. BA showed better results than ACT regarding impact on anxiety and activation. This greater efficacy may have been due to factors such as the emphasis placed in BA on behavioural activation and the central role played in it by functional analysis. The key role played by experiential avoidance and behavioral activation in the maintenance and treatment of emotional problems in cancer survivors is discussed. Raw data are available online (http://dx.doi.org/10.17632/m7w688khs8.1 )